The strategic implications of formation of regional industrial cluster by pluralistic approaches of the regional employment analysis and the competitive development model - Ito Akio; Hideaki Abe (European Regional Science Association (ERSA), 2002)
The purpose of this study is to consider the strategic implications of formation of regional industrial cluster, especially Kitami region in Japan. At present, Japanese government is wrestling with great problems as the structural reform of Japanese economy and reconstruction of public finance in Japan etc. In this situation, how to inovate the regions of Japan is very important and difficult subject. The regional innovation is complex phenomenon. Accordingly it should be use the complex approach naturally. However, only few attempts have so far been made at complex approach of regional industrial cluster. Therefore, in this study we use the pluralistic approaches of regional economics and management economics and to consider about regional industrial cluster strategically. As the result, this study lead to the below strategic implications. First, the accurate perception of development's phase on the region is very important. Second, the involvement and role of government is very important too. Third, to make the plan of regional industrial cluster on the region is necessary as the driving force towards the goal.
Keywords: 330